2019
DOI: 10.1111/anec.12651
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic circulating endothelial progenitor cells are linked to electrocardiographic conduction abnormalities in rheumatic patients

Abstract: Background: Osteogenic circulating endothelial progenitor cells (EPC) play a patho-genic role in cardiovascular system degeneration through promulgating vasculature calcification, but its role in conduction disorders as part of the cardiovascular degenerative continuum remained unknown. Aim: To investigate the role of osteocalcin (OCN)-expressing circulating EPCs in cardiac conduction disorders in the unique clinical sample of rheumatoid arthritis (RA) susceptible to both abnormal bone metabolism and cardiac c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…While circulating endothelial progenitor cells (EPC) were believed to generally play a protective role in ameliorating vascular insults by homing to sites of vascular injury and promoting re-endothelialization, 1 recent studies revealed that sub-progenies of EPC that express the osteoblastic marker, namely osteocalcin (OCN), could have detrimental effects in promoting cardiovascular calcification and aging. 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…While circulating endothelial progenitor cells (EPC) were believed to generally play a protective role in ameliorating vascular insults by homing to sites of vascular injury and promoting re-endothelialization, 1 recent studies revealed that sub-progenies of EPC that express the osteoblastic marker, namely osteocalcin (OCN), could have detrimental effects in promoting cardiovascular calcification and aging. 2–4 …”
Section: Introductionmentioning
confidence: 99%